The usefulness of a combination of age, body mass index, and blood urea nitrogen as prognostic factors in predicting oxygen requirements in patients with coronavirus disease 2019. Issue 12 (December 2021) - Goto, Norihiko; Wada, Yosuke; Ikuyama, Yuichi; Akahane, Jumpei; Kosaka, Makoto; Ushiki, Atsuhito; Kitaguchi, Yoshiaki; Yasuo, Masanori; Yamamoto, Hiroshi; Matsuo, Akemi; Hachiya, Tsutomu; Ideura, Gen; et al.
Abstract: Introduction: Risk factors for seriously ill coronavirus disease 19 (COVID-19) patients have been reported in several studies. However, to date, few studies have reported simple risk assessment tools for distinguishing patients becoming severely ill after initial diagnosis. Hence, this study aimed to develop a simple clinical risk nomogram predicting oxygenation risk in patients with COVID-19 at the first triage. Methods: This retrospective study involved a chart review of the medical records of 84 patients diagnosed with COVID-19 between February 2020 and March 2021 at ten medical facilities. The patients were divided into requiring no oxygen therapy (non-severe group) and requiring oxygen therapy (severe group). Patient characteristics were compared between the two groups. We utilized univariate logistic regression analysis to confirm determinants of high risks of requiring oxygen therapy in patients with moderate COVID-19. Results: Thirty-five patients ware in severe group and forty-nine patients were in non-severe group. In comparison with patients in the non-severe group, patients in the severe group were significantly older with higher body mass index (BMI), and had a history of hypertension and diabetes. Serum blood urea nitrogen (BUN), lactic acid dehydrogenase (LDH), and C-reactive protein (CRP) levels were significantly higher in the severe group. Multivariate analysis showed that older age, higher BMI, and higher BUN levels were significantly associated with oxygen requirements. Conclusions: This study demonstrated that age, BMI, and BUN were independent risk factors in the moderate-to-severe COVID-19 group. Elderly patients with higher BMI and BUN require close monitoring and early treatment initiation.